Analysis of Interactions between Telomeric i‐Motif DNA and a Cyclic Tetraoxazole Compound. (12th October 2018) - Sedghi Masoud, Shadi; Yamaoki, Yudai; Ma, Yue; Marchand, Adrien; Winnerdy, Fernaldo Richtia; Gabelica, Valérie; Phan, Anh Tuân; Katahira, Masato; Nagasawa, Kazuo
Abstract: The interaction of a macrocyclic tetraoxazole compound, L2H2‐4OTD (1 ), with two aminoalkyl side chains and telomeric i‐motif, was investigated by means of electrophoretic mobility shift assay, circular dichroism spectroscopy, mass spectrometry and NMR spectroscopy analyses. The results indicate that1 interacts with the i‐motif structure at two preferred binding sites. Abstract : Pinpointing binding sites : A cyclic tetraoxazole compound that contains the i‐motif as an interacting agent has been synthesised. The interaction of this compound with the telomeric i‐motif has been analysed by means of NMR spectroscopy to reveal two preferred binding sites.